Foreign body aspiration and mucormycosis: a case report - Mehdinezhad, Hamed; Mohseni Ahangar, Reza; Golparvar Azizi, Mohammad; Ghasemian, Mohammad; Yari, Zahra; Jafarian, Elham; Tavakoli Pirzaman, Ali (Frontiers in Medicine, 2023)
Over the course of the Coronavirus disease 2019 (COVID-19) pandemic, numerous complications have been documented. In this report, we have detailed an unexpected complication of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection that occurred in a 73-year-old female patient who was simultaneously afflicted with mucormycosis and another unanticipated problem. Due to the lack of recovery of the patient after receiving mucormycosis treatment and continued fever, cough and hemoptysis, bronchoscopy was performed for her. During bronchoscopy, we encountered a foreign body that was the cause of the patient’s fever, cough, and hemoptysis. Rigid bronchoscopy was performed and the foreign body was removed from the left main bronchus. The lack of a favorable treatment response after administering antifungal therapy suggested that the presence of a foreign body could potentially act as an underlying nidus, thus influencing the suboptimal therapeutic outcome. Mucormycosis is usually characterized by distinct radiological patterns. However, this case did not present predictable imaging findings, further complicating the diagnostic process associated with this invasive fungal infection.